1975
DOI: 10.1002/prac.19753170404
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Preparation and Properties of Molybdenum Oxy Phenoxides

Abstract: Reactions of molybdenum oxy tetrachloride with mono‐, di‐, and trihydroxy phenols have been carried out and molybdenum oxy phenoxides isolated. Alternative method for the preparation of these oxy phenoxides by the interaction between molybdenum oxy tetraethoxide and corresponding phenols has been reported. I. R. spectra of the oxy phenoxides have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…9 The molybdenum(VI) complex is photolabile and prone to disproportionation to chlorine and Mo(V) products, and it must be freshly prepared before use. 10 Although there is an old report of MoOCl 4 + ArOH yielding the corresponding oxo aryloxides, 11 this has never been confirmed and was not reproducible by us. Hayano et al reported the successful formation of MoO(OAr) 4 for several mono-and multidentate aryloxy ligands by the low-temperature reaction of MoOCl 4 with the corresponding aryloxy anions, but the yields are low and the characterization minimal.…”
mentioning
confidence: 84%
“…9 The molybdenum(VI) complex is photolabile and prone to disproportionation to chlorine and Mo(V) products, and it must be freshly prepared before use. 10 Although there is an old report of MoOCl 4 + ArOH yielding the corresponding oxo aryloxides, 11 this has never been confirmed and was not reproducible by us. Hayano et al reported the successful formation of MoO(OAr) 4 for several mono-and multidentate aryloxy ligands by the low-temperature reaction of MoOCl 4 with the corresponding aryloxy anions, but the yields are low and the characterization minimal.…”
mentioning
confidence: 84%